PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALTY UNTUK MENINGKATKAN MINAT BELAJAR DAN HASIL BELAJAR SISWA DI KELAS III SD AL KAUTSAR - Shintya Putri Kartika; Muhajir; Soesiana Tri Eka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research conducted is a type of research and development that aims to: (1) produce products in the form of Augmented Reality learning media that are feasible and effective for the learning activities of students in grade III-A SD Al Kautsar Surabaya. (2) The development model used is the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. (3) Data collection using validation test questionnaire instruments for media experts, material experts, students and pre-test and post-test questions. (4) The results of the study show that the learning media is declared valid or feasible based on the validity test by: a. Media experts obtained 100% results with feasible/valid criteria, b. Material Experts obtained 100% results with feasible/valid criteria, c. students obtained 91.1% results with feasible criteria, d. The student learning outcome test of 28 students had an average score of 69.29 in the pre-test results while the average score obtained in the post-test results was 86.79 so that the learning outcomes increased. From the results of the above trial, it can be concluded that the Augmented Reality learning animation media of metamorphosis material is declared effective in the learning process of science subjects of Metamorphosis material for grade III students of SD Al Kautsar Surabaya.